Synthesis and proton conducting ability of a crystalline 3-D vanadoborate with [V6B20] architectures. (31st January 2023) - Liu, Xinxin; Wang, Xianyu; Guo, Biao; Zhao, Sisi; Zhou, Lijing; Kong, Lian; Zhao, Zhen
Abstract : A 3-D vanadoborate based on the rare [V6 B20 ] cluster was successfully synthesized and exhibits good proton conductivity. Abstract : A new crystalline three-dimensional (3-D) vanadoborate (H2 en)4 [(VO)6 (B10 O22 H4 )2 (H2 O)]·4H2 O (1, H2 en = NH3 CH2 CH2 NH3 ), based on the lantern-type [(VO)6 (B10 O22 H4 )2 (H2 O)] cluster (denoted as [V6 B20 ]), was successfully synthesized employing a hydrothermal reaction. In the structure, H2 en 2+ cations and H2 O molecules are accommodated in the intercluster space of the framework and interact with the [V6 B20 ] polyanions via hydrogen bonds (N–H⋯O and O–H⋯O), through which the respective molecular species are integrated into 3-D architectures. The presence of adequate guest ions and molecules ( i.e., H2 en 2+ and H2 O), and abundant H-bonding networks in the resulting channels imparts humidity- and temperature-dependent proton conducting ability to compound 1 . Strikingly, at 333 K and 100% RH, compound 1 exhibits a good proton conductivity of 8.82 × 10 −4 S cm −1, with the magnitude comparable to that of other excellent MOF-based proton conductors. A high activation energy of 0.48 eV for 1 indicates that the proton migration in this compound is mainly governed by vehicle mechanism, combined with the synergic Grotthuss mechanism.